Association of high-density lipoprotein levels with baseline coronary plaque volumes by coronary CTA in the EVAPORATE trial. (July 2020) - Lakshmanan, Suvasini; Shekar, Chandana; Kinninger, April; Dahal, Suraj; Onuegbu, Afiachukwu; Cai, Andrew N.; Hamal, Sajad; Birudaraju, Divya; Cherukuri, Lavanya; Flores, Ferdinand; Dailing, Christopher; Roy, Sion K.; et al.
Abstract: Background and aims: Dyslipidemia with elevated triglycerides (TGL) and low high-density lipoprotein cholesterol (HDL-C) predicts residual cardiovascular risk, despite goal LDL-C levels and optimal statin therapy. Coronary plaque characterization by CCTA can provide mechanistic understanding of coronary artery disease and associated prognosis. The role of HDL-C in the pathogenesis of atherosclerosis is not well understood in statin-treated patients with elevated TGL. We sought to examine the association of HDL-C levels with baseline coronary plaque volumes, namely total plaque (TP) and total non-calcified plaque (TNCP) volumes by CCTA in participants enrolled in the EVAPORATE trial. Methods: We analyzed 80 participants who were enrolled in the trial. Linear regression analysis as a univariate and multivariate model adjusted for significant cardiovascular risk factors was performed to evaluate independent association of HDL-C and baseline coronary plaque volumes. In an exploratory analysis, stratified by sex, we compared the association of serum HDL-C levels with baseline coronary plaque volumes in males and females. Results: Mean (SD) age of participants (n = 80) was 57.1 (8.6) years and 43% were male. Median (Inter Quartile Range/IQR) log-TNCP volume was 83.0 (0.1–7.3) mm 3 and median (IQR) log-TP volume was 144.8 (0.1–7.1) mm 3 . After adjustment for relevant clinical covariates including age, gender, BMI, hypertension, diabetes, past smoking and baseline TGL levels, increasing levels of HDL-C remain independently associated with lower baseline log-TNCP volumes (β: 0.043 ± 0.021, p = 0.042) and baseline log-TP volumes (β: 0.046 ± 0.022, p = 0.035) on CCTA. On stratifying by sex in a multivariable regression analysis, HDL-C levels were inversely associated with baseline log-TNCP volumes (β: 0.066 ± 0.026, p = 0.018) and log-TP volumes (β: 0.077 ± 0.025, p = 0.004) in females, but not in males (log-TNCP volumes β: 0.038 ± 0.034, p = 0.282) and log-TP volumes (β: −0.033 ± 0.036, p = 0.364). Conclusions: In a cohort of statin treated patients with known atherosclerosis and residually elevated TGL, there was a significant inverse relationship between HDL-C levels and baseline coronary plaque, TP and TNCP volumes on CCTA. Our findings provide more detailed mechanistic evidence regarding the protective role of HDL-C in coronary atherosclerosis in a high-risk cohort. Further investigation to evaluate the interaction of HDL-C levels and coronary plaque volumes on differential CVD risk in statin-treated patients with elevated TGL levels is warranted. Graphical abstract: Image 1 Highlights: Dyslipidemia with elevated triglycerides (TGL) and low high-density lipoprotein cholesterol (HDL-C) predicts residual cardiovascular risk, despite goal LDL-C levels and optimal statin therapy. In our study, HDL-C levels were associated with decreasing volumes of baseline coronary plaque volumes on CCTA in statin treated participants with elevated TGL, enrolled in the EVAPORATE trial. Our findings provides mechanistic evidence for the protective role of HDL-C in coronary atherosclerosis in a vulnerable cohort of statin-treated patients with at-goal LDL-C levels and residually elevated TGL.